Α2A adrenergic receptors highly expressed in mesoprefrontal dopamine neurons. (22nd September 2016) - Castelli, M. Paola; Spiga, Saturnino; Perra, Andrea; Madeddu, Camilla; Mulas, Giovanna; Ennas, M. Grazia; Gessa, Gian Luigi
Highlights: α2A-adrenoceptors mRNA are shown in VTA DA neurons. α2A-adrenoceptors mRNA are higher in VTA than substantia nigra DA neurons. α2A-adrenoceptors are much higher in mesoprefrontal than nigrostriatal DA neutrons. Do α2A-adrenoceptors subserve autoreceptor role in mesoprefrontal DA neurons? Abstract: α2 adrenoreceptors (α2-ARs) play a key role in the control of noradrenaline and dopamine release in the medial prefrontal cortex (mPFC). Here, using UV-laser microdissection-based quantitative mRNA expression in individual neurons we show that in hTH-GFP rats, a transgenic line exhibiting intense and specific fluorescence in dopaminergic (DA) neurons, α2A adrenoreceptor (α2A-AR) mRNA is expressed at high and low levels in DA cells in the ventral tegmental area (VTA) and substantia nigra compacta (SNc), respectively. Confocal microscopy fluorescence immunohistochemistry revealed that α2A-AR immunoreactivity colocalized with tyrosine hydroxylase (TH) in nearly all DA cells in the VTA and SNc, both in hTH-GFP rats and their wild-type Sprague–Dawley (SD) counterparts. α2A-AR immunoreactivity was also found in DA axonal projections to the mPFC and dorsal caudate in the hTH-GFP and in the anterogradely labeled DA axonal projections from VTA to mPFC in SD rats. Importantly, the α2A-AR immunoreactivity localized in the DA cells of VTA and in their fibers in the mPFC was much higher than that in DA cells of SNc and their fibers in dorsal caudate, respectively. The finding that α2A-ARs are highly expressed in the cell bodies and axons of mesoprefrontal dopaminergic neurons provides a morphological basis to the vast functional evidence that somatodendritic and nerve-terminal α2A-AR receptors control dopaminergic activity and dopamine release in the prefrontal cortex. This finding raises the question whether α2A-ARs might function as autoreceptors in the mesoprefrontal dopaminergic neurons, replacing the lack of D2 autoreceptors.